Antecedent and Mediator of Actual Visit Behavior Amongst International Tourists in Jordan - Al Muala, Ayed (2010)
Actual visit behavior has been for many years an area of ongoing interest in fields that span both tourist behavior and international marketing. Despite the growth of the tourism industry, hotel industry is facing fluctuating tourist revisit intention provoked by dissatisfaction, high travel risk, mediocre hotel service, or negative Jordan image. Moreover, considerable fragmentation and inconsistency in empirical findings has limited theory development. This thesis, which is based on the concepts of Theory of Planned Behavior (TPB), has the following objectives: (1) to identify the direct influence of (perceived risk, revisit intention and perceived behavior control) on actual visit behavior. (2) to identify the direct influence of (tourist satisfaction, tourist attitude, subjective norm and perceived behavior control) on revisit intention. (3) to identify the direct influence of (perceived risk, Jordan image and service climate) on tourist satisfaction. (4) to examine to what extent revisit intention and tourist satisfaction mediate the relationship between perceived risk and actual visit behavior. (5) to determine the mediating effect of revisit intention on linkage of perceived behavior control with actual visit behavior. (6) to determine how the underpinning theory of Planned Behavior (TPB) can be used to explain actual visit behavior in Jordan. The measurement for the latent variables is adopted from past studies as follows: tourist satisfaction (10 items); perceived risk (7 items); Jordan image (11 items); service climate (10); revisit intention (5); tourist attitude (6 items); subjective norm (6 items); perceived behavior control (6 items); actual visit behavior (5 items). From 850 samples, 494 usable responses were returned representing a 59% response rate. Using Structural Equation Modelling (SEM), the Generating (MG) achieved model fit as shown in the GOF index: Ratio (CMIN/df) =1.186; GFI=0.973; RMSEA= 0.019; TLI=0.991; P-value=0.096. The SMC = 0.703 which means that the predictors explain 70.3% variance in actual visit behavior. The findings highlight five direct significant antecedents of actual visit behavior: revisit intention ( =.264, CR=2.720 p=0.007), perceived risk ( =-.318, CR= -2.197 p=0. 028), subjective norm ( =.199, CR=2.112 p=.035), Jordan image ( =.504, CR=2.653 p=.008) and service climate ( =.226, CR=3.020 p=.003); three direct significant antecedents of intention: tourist satisfaction ( =.373, CR=5.400 p=***), tourist attitude ( =.182, CR= 2.734 p=.006), subjective norm ( =.262, CR= 4.178 p=***); three direct significant antecedents of satisfaction: Jordan image ( =.356, CR=2.407 p=.016), subjective norms ( =173, CR=2.343 p=.019) and perceived behavior control ( =.159, CR=2.117 p=.034). The study found two insignificant direct antecedents to actual visit behavior PBC and satisfaction; one insignificant direct antecedents of intention i.e. PBC; three insignificant direct antecedents of satisfaction i.e. service climate and attitude. The finding supports eleven hypotheses (H1, H2, H3, H4, H7, H9, H4a, H9a, H10a, H4b, and H5a) and rejects six hypotheses (H5, H6, H8, H10, H2a, and H3a). Satisfaction and intention were found to be non-mediators.